Neonatal complications in public and private patients: a retrospective cohort study. Issue 5 (28th May 2013) - Einarsdóttir, Kristjana; Stock, Sarah; Haggar, Fatima; Hammond, Geoffrey; Langridge, Amanda T; Preen, David B; De Klerk, Nick; Leonard, Helen; Stanley, Fiona J
Abstract : Objective: To use propensity score methods to create similar groups of women delivering in public and private hospitals and determine any differences in mode of delivery and neonatal outcomes between the matched groups. Design: Population-based, retrospective cohort study. Setting: Public and private hospitals in Western Australia. Participants: Included were 93 802 public and 66 479 private singleton, term deliveries during 1998–2008, from which 32 757 public patients were matched with 32 757 private patients on the propensity score of maternal characteristics. Main outcome measures: Neonatal outcomes were compared in the propensity score-matched cohorts using conditional logistic regression, adjusted for antenatal risk factors and mode of delivery. Outcomes included Apgar score <7 at 5 min, neonatal resuscitation (endotracheal intubation or external cardiac massage) and admission to a neonatal special care unit. Results: No significant differences in maternal characteristics were found between the propensity score-matched groups. Private patients were more likely than their matched public counterparts to undergo prelabour caesarean section (25.2% vs 18%, p<0.0001). Public patients had lower rates of neonatal unit admission (AOR 0.67, 95% CI 0.62 to 0.73) and neonatal resuscitation (AOR 0.73, 95% CI 0.56 to 0.95), but higher rates of low Apgar scores at 5 min (AOR 1.31, 95% CI 1.06 to 1.63) despite adjustment for antenatal factors. Additional adjustment for mode of delivery reduced the resuscitation risk (AOR 0.86, 95% CI  0.63 to 1.18) but did not significantly alter the other estimates. Conclusions: Propensity score methods can be used to generate comparable groups of public and private patients. Despite the rates of low Apgar scores being higher in public patients, the rates of special care admission were lower. Whether these findings stem from differences in paediatric services or clinical factors is yet to be determined.